Efficacy and safety of LongShengZhi capsule on functional recovery after acute ischemic stroke (LONGAN): Protocol and statistical analysis plan for a randomized, double-blind, placebo-controlled trial - Zhang, Dandan; Li, Tingting; Wang, Anxin; Feng, Luda; Lai, Xinxing; Cao, Kegang; Zhou, Li; Yang, Baolin; Cui, Fangyuan; Li, Qingbin; Dou, Jinjuan; Qi, Baoyun; et al. (Frontiers in Pharmacology, 2022)
Background: Due to limited time windows and technical requirements, only a small percentage of patients can receive reperfusion therapy for acute ischemic stroke (AIS). Previous studies have shown that LongShengZhi (LSZ) capsule can improve neurological outcomes in patients after AIS, yet those results have not been finally verified through rigorous randomized controlled trials. Thus, this trial was designed to further clarify the efficacy and safety of LSZ capsule for patients with AIS. Methods: LSZ capsule on Functional Recovery after Acute Ischemic Stroke (LONGAN) trial is a prospective, multicenter, randomized, placebo-controlled, double-blind, parallel-group, superiority trial that enrolls patients from stroke and rehabilitation units in China. We will enroll 1376 patients aged 18 years or older with AIS within 7 days of symptom onset and a National Institute of Health Stroke Scale (NIHSS) score of 4–15. Eligible patients will be randomized to receive either 2 g LSZ capsules three times a day or placebo LSZ capsules for 90 days. The primary outcome is the proportion of patients with favorable outcomes, as measured by the modified Rankin Scale (mRS) 90 days after randomization. The main safety outcome is the proportion of severe adverse events. Conclusions: This study will be the first randomized, double-blind trial to evaluate the efficacy and safety of LSZ capsule in patients with AIS. In order to improve the transparency and reproducibility of the trial, the data will be analyzed in accordance with this pre-specified plan for statistical analysis to reduce bias due to selective analysis and reporting. This trial aims to provide high-quality evidence for the efficacy and safety of LSZ capsule for AIS.